An estimate of the remainder term in the central limit theorem for $r$-independent random variables - Sharakhmetov, Sh. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We suggest a method for the investigation of $r$-independent random variables by using multiplicative systems. An estimate of the remainder term in the central limit theorem for $r$-independent random variables is obtained.